Antibiotic resistant Escherichia coli from diarrheic piglets from pig farms in Thailand that harbor colistin-resistant mcr genes - Nguyet L.T.Y. (2023)
Antibiotic-resistant Escherichia coli is one of the most serious problems in pig production. This study aimed to determine the antibiotic susceptibility and genotypes profiles of diarrhoeagenic E. coli that causes diarrhea in piglets. Thirty-seven pathogenic E. coli strains were used in this study. These were isolated from rectal swabs of diarrheic piglets from farms in Thailand from 2018 to 2019. Escherichia coli isolates were highly resistant to amoxicillin (100%), followed by oxytetracycline (91.9%), enrofloxacin (89.2%), trimethoprim/sulfamethoxazole (86.5%), amoxicillin: clavulanic acid (81.1%), colistin and gentamicin (75.7%), ceftriaxone and ceftiofur (64.9%), ceftazidime (35.1%) and 97.3% showed multidrug-resistance (MDR). There were 8 (21.6%) mcr-1 carriers, 10 (27.0%) mcr-3 carriers and 10 (27.0%) co-occurrent mcr-1 and mcr-3 isolates. The phenotype-genotype correlation of colistin resistance was statistically significant (performed using Cohen’s kappa coefficient (κ = 0.853; p < 0.001)). In addition, PCR results determined that 28 of 37 (75.7%) isolates carried the int1 gene, and 85.7% int1-positive isolates also carried the mcr gene. Genetic profiling of E. coli isolates performed by ERIC-PCR showed diverse genetics, differentiated into thirteen groups with 65% similarity. Knowledge of the molecular origins of multidrug-resistant E. coli should be helpful for when attempting to utilize antibiotics in the pig industry. In terms of public health awareness, the possibility of transmitting antibiotic-resistant E. coli from diarrheic piglets to other bacteria in pigs and humans should be of concern.